Epidemiologi, Stadium, dan Derajat Diferensiasi Kanker Kepala dan Leher - Nelsiani To'Bungan; Siti Hamidatul A'liyah; Nastiti Wijayanti; Jajah Fachiroh (Department of Biology, Faculty of Sci and Tech, Universitas Islam Negeri Alauddin Makassar, 2015)
Head and neck cancer is one of the deadly types of cancer in Indonesia. The main cause of this cancer is the consumption of alcohol and cigarettes. Head and neck cancer attacks the lips, mouth, palate, pharynx and larynx. Studies about head and neck cancer have been carried out in westerncountries, while in Indonesia is still limited. Earlier studies in western countries expressed that head and neck cancer is more common in men than women. Purpose of research were to determine the epidemiology of head and neck cancer in Indonesia related to patient ratio of men and women andthe correlation of stage and differentiation level of head and neck cancer. Data were obtained from the Rumah Sakit Kanker Dharmais-Pusat Kanker Nasional Jakarta and then analyzed descriptively. The data were analyzed came from 36 patients with head and neck cancer. The results showed, menwith head and neck cancer as much as 52,77% and females 47,22%. There were 16 cases with stage IV cancer, 9 with stage III, 8 with stage II and 2 with stage I. There were 6 cases of stage IV cancer with better differentiation, and there were 2 cases of stage II cancer with a poor differentiation. Head and neck cancer is more common in men than women. There was no correlation between the degree of differentiation-stage head and neck cancer. It was influenced by immunity of each person.Keywords: differentiation level, epidemiology, head and neck cancer, stage